2004
DOI: 10.1038/modpathol.3800093
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous carcinoma of the colon: correlation of loss of mismatch repair enzymes with clinicopathologic features and survival

Abstract: Colorectal carcinoma with microsatellite instability (MSI-H) has a characteristic clinicopathologic profile, typically forming right-sided, lymphocyte-rich tumors that are often mucinous. Mucinous histology in general has been linked to adverse prognosis in some studies, but not in others. MSI-H carcinoma, in contrast, has a better prognosis than microsatellite stable carcinoma in most studies. We assessed the relationship between MSI status, clinicopathologic features and outcome for 248 consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
93
2
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 33 publications
14
93
2
5
Order By: Relevance
“…In agreement with previous reports, 20,21 univariate analysis demonstrated that lower TNM stage and absence of vascular invasion had a favorable effect on survival of mucinous adenocarcinoma patients. Decreased invasion depth and no lymph node metastasis also had a favorable effect on survival of mucinous adenocarcinoma patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with previous reports, 20,21 univariate analysis demonstrated that lower TNM stage and absence of vascular invasion had a favorable effect on survival of mucinous adenocarcinoma patients. Decreased invasion depth and no lymph node metastasis also had a favorable effect on survival of mucinous adenocarcinoma patients.…”
Section: Discussionsupporting
confidence: 92%
“…Higher TNM stage was an independent predictor of poor outcome in patients with mucinous adenocarcinoma, which is in accordance with other studies. 20,21 In univariate analysis, lower TNM stage had a favorable effect on survival of signet-ring cell carcinoma patients; this finding is consistent with other reports. 3,6 The vast majority of signet-ring cell carcinoma presents as a diffusely infiltrating carcinoma, which therefore is described by some authors as linitis plastica or lymphangiosis-type colorectal carcinoma.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Em geral, os tumores com áreas mucoprodutoras usualmente são encontrados em estádios mais avançados de doença, com maior invasão dos tecidos periviscerais e metástases em linfonodos regionais mais freqüentemente. O prognóstico dos pacientes com adenocarcinoma colorretal está relacionado ao número de linfonodos regionais comprometidos por metástases e a profundidade de invasão da parede (6,9,14,16,17,18,19,20) . Os autores não encontraram associação significativa entre a presença de metástases em linfonodos regionais com idade (p=0,802), sexo (p=0,786), borda de invasão tumoral microscópica (p=0,180), presença de áreas mucoprodutoras (p=0,860), grau de diferenciação tumoral (p=0,068) e tamanho tumoral (p=0,987).…”
Section: Discussionunclassified